Long-term effects and significant Adverse Drug Reactions (ADRs) associated with the use of Gonadotropin-Releasing Hormone analogs (GnRHa) for central precocious puberty: a brief review of literature - De Sanctis, Vincenzo; Soliman , Ashraf T; Di Maio, Salvatore; Soliman, Nada; Elsedfy, Heba (Acta Biomedica Atenei Parmensis, 2019)
Central precocious puberty (CPP) is defined as an early pubertal development that occurs before the age of 9 years in boys and 8 years in girls. It results from premature activation of the hypothalamic-pituitary-gonadal axis. Gonadotropin-releasing hormone agonists (GnRHa) have been the gold standard therapy for CPP for more than 30 years. These compounds have a high affinity for the pituitary LHRH receptor and are resistant to enzymatic degradation. Through continuous stimulation, GnRHa inhibit the pulsatile secretion of gonadotropin, resulting in hormonal suppression, cessation of pubertal development, and normalization of growth and skeletal maturation rates. The goal of therapy is to halt pubertal progression and delay epiphyseal maturation that leads to improvement of final adult height. There are no widely accepted guidelines for how long to continue treatment with a GnRHa for CPP, and individual practice varies widely. Furthermore, conflicting results have been published on the long-term effects of GnRHa therapy in patients with CPP. Therefore, we reviewed the current literature focusing our attention on the long-term effects and the significant adverse drug reactions (ADRs) observed during treatment with GnRHa in patients with CPP. Our review may provide the necessary data to enable clinicians to administer GnRHa in the safest and most appropriate way. Further studies are necessary to identify the mechanisms of development of potential adverse drug reactions related to GnRHa therapy in CPP.